The Multiple Influences on the Future of Work in Agriculture: Global Perspectives - Dedieu, Benoit; Contzen, Sandra; Nettle, Ruth; Schiavi, Sandra Mara de Alencar; Sraïri, Mohamed Taher (Frontiers in Sustainable Food Systems, 2022)
In this introductory paper, we discuss changes in work in agriculture arising from the influence of a wide variety of factors: global food chains and societal controversies about farming models, the status of agricultural work as a profession alongside others; the progress of rural development; issues of precariousness in work and in health. We summarize these influences and their implications to introduce the Special Issue “Work in agriculture: which perspectives?”, and outline the seven papers that contribute to understanding of the future trajectories for work in agriculture.